Crise da zona do Euro: uma perspectiva de análise - Pereira, Emelson Macedo Martins (2016)
There is a turbulence in the recent history of the common European currency. The public debt crisis in the Eurozone has caused discussions about the monetary integration process. Until then, the Economic and monetary european union served as a reference for agreements such as Mercosur and NAFTA. In recent years, as an effect of the global economic crisis of 2008, a strong deficit increase has occurred in the Eurozone’s countries due to the need to stimulate demand and prevent bankruptcy of large private banks. Consequently, the public debt crisis in Greece, Italy, Ireland, Portugal and Spain creates uncertainty about the euro’s future. The public expenditure cuts, freezing of salaries, pensions and tax increment were immediate alternatives to contain deficits. Political and economic differences re-emerged on the continent, undermining the pact resulting from attempts to integrate the continent economically and politically. Thus, the European Union is experiencing the most controversial situation in its history. The main objective of this research is to understand the roots of the European economic crisis and investigate instruments for its containment, permeating the orthodox, keynesian and marxist paradigms